Enhancement of effective electromechanical coupling factor by mass loading in layered surface acoustic wave device structures. (9th June 2016) - Tang, Gongbin; Han, Tao; Teshigahara, Akihiko; Iwaki, Takao; Hashimoto, Ken-ya
Abstract: This paper describes a drastic enhancement of the effective coupling factor by mass loading in layered surface acoustic wave (SAW) device structures such as the ScAlN film/Si substrate structure. This phenomenon occurs when the piezoelectric layer exhibits a high acoustic wave velocity. The mass loading decreases the SAW velocity and causes SAW energy confinement close to the top surface where an interdigital transducer is placed. It is shown that this phenomenon is obvious even when an amorphous SiO2 film is deposited on the top surface for temperature compensation. This enhancement was also found in various combinations of electrode, piezoelectric layer, and/or substrate materials. The existence of this phenomenon was verified experimentally using the ScAlN film/Si substrate structure.